Broadband electromagnetic wave absorption using pure carbon aerogel by synergistically modulating propagation path and carbonization degree - Su, Xiaogang; Wang, Jun; Han, Mengjie; Liu, Yanan; Zhang, Bin; Huo, Siqi; Wu, Qilei; Liu, Yaqing; Xu, He-Xiu (Journal of colloid and interface science, 2023)
[Display omitted] Carbon materials were widely used as electromagnetic (EM) wave absorption due to their advantages of light weight, environmental resistance and high electrical conductivity. However, conventional means were typically available by combining carbon and other materials to achieve effective absorption. Herein, a novel strategy using pure carbon aerogel with oriented structure was reported to enhance the EM wave absorption by synergistically modulating the wave propagation path and carbonization degree. The aerogel contained proposed modified carbon nanofibers (MCNF) derived from bacterial cellulose (BC), and core-shell carbon nanofibers @ reduced oxide graphene (CNF@RGO). The oriented structure was induced by the temperature field, which manifests anisotropic EM constitutive parameters (εx ≠ εz) at different directions of incident wave. The carbonization degree was adjusted by varying the carbonization temperature. At the carbonization temperature of 700 °C, the maximum reflection loss and effective absorption bandwidth reached −53.94 dB and 7.14 GHz, respectively, enabling the aerogel to outperform its previous counterparts. To clarify the EM wave mode-of-action in conjunction, physical models of the aerogel were established in addition to finite element simulation and theoretical analysis. Notably, the aerogel with a density of 3.6 mg/cm3 featured ultra-light weight, superhydrophobicity, superior compressibility, and thermal insulation. Our work offers an efficient strategy for designing broadband and multifunctional EM wave absorption materials (EWAMs), promising great potentials in complex stealth equipment.